THE WORLD EXPERIENCE IN PUBLIC PRIVATE PARTNERSHIP PROJECTS - Karimov Akramjon Ikromjon ugli; Turayev Anvar Shokirovich (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The public-private partnership (PPP) model has been increasingly popular in recent decades as a mechanism to support infrastructure related investment activity. PPPs creates many advantages for countries such as releasing from financial burden of high cost infrastructure investments, bringing high quality of public service and increasing efficiency of operations through transfer of private sector expertise.